Psychosocial Support during COVID-19 Pandemic - Amgain, Ganesh; Pokharel, Rishika (Journal of Karnali Academy of Health Sciences, 2021)
Amid COVID-19 pandemic, the entire world is having to deal with the physical and mental health crisis along with the different psychosocial issues. Alarming number of deaths globally has made the people survive a strict lockdown, shutdown and prohibition period which accelerated adaptive and maladaptive human responses to the crisis. These maladaptive human responses are correlated with adverse physical and mental health issues. During the time of pandemic, primary symptomatic treatments along with the preventive measures psychosocial support is crucial to better deal with the global crisis. The most significantly recommended psychosocial support during COVID-19 includes; staying informed, focusing on self-care, connecting to others virtually, taking time for physical activities, making schedules and seeking for help if needed.